Screening of phytoconstituents and antibacterial activity of leaves and bark of Quercus leucotrichophora A. Camus from Uttarakhand Himalaya - Prabhakar Semwal (Clinical Phytoscience, 2018)
Abstract Background Quercus leucotrichophora A. Camus (QL) belongs to the family Fagaceae, commonly known as Banj oak in the Garhwal region of Himalaya, where it is the principal source of fuel, fodder, and medicine. Methods In the present study, GC-MS analysis has been performed for profiling the chemical composition of methanolic extracts of leaves and bark of QL. The antibacterial activity was evaluated by using the disk diffusion method against five bacterial strains. Results Total 23 components in bark and 62 components in leaves extracts of QL were identified. The major components identified in the bark extracts were Linoleic acid (19.77%), Lupeol (17.91%), Epi-psi-Taraxastanonol (14.20), and cis-Vaccenic acid (13.10%), while others were present in relatively small amounts. For the leaves extract, the major components were Linoleic acid (17.09%), Simiarene (15.29%), Flavone 4′-oh, 5-oh,7-di-o-glucoside (15.26%), and D-Quinic acid (9.29%), respectively. As far as antibacterial assays are concerned, it was observed that both the extracts are active against most of the tested bacterial strains with the zone of inhibition ranging between 8.53 ± 0.50 to 19.07 ± 0.31 mm, respectively. Conclusion The GC-MS results revealed the presence of several phytochemical compounds in leaves and bark of QL extract and are recommended as a plant of pharmaceutical importance. The antibacterial analysis showed that both the extracts (leaves and bark) of QL have antibacterial activity against all gram positive (S. aureus, B. subtilis and S. pyogenes) and gram negative (E. coli, P. aeruginosa) bacterial strains.